If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12z + -10z + -2 = 2 Reorder the terms: -2 + 12z + -10z = 2 Combine like terms: 12z + -10z = 2z -2 + 2z = 2 Solving -2 + 2z = 2 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2z = 2 + 2 Combine like terms: -2 + 2 = 0 0 + 2z = 2 + 2 2z = 2 + 2 Combine like terms: 2 + 2 = 4 2z = 4 Divide each side by '2'. z = 2 Simplifying z = 2
| 5x+6x-2x=43+2 | | rv+3*1v-3=0 | | 7-2.5x=13 | | 1.09(1.23)(7-x)=9 | | (X-28)+(2x-79)+(.5x+14)=180 | | 4x^2-30x+44=0 | | 50=36.5+.1m | | 150=2x+5(-7x-3) | | 2(p+3)=14 | | -2x+8=-144 | | -14f=-13f-14 | | 19x+12=18x+3 | | 4j-9j+j-4j-5= | | 2/3x^2-7=46 | | 0.2(18)+0.05x=0.1(24+x) | | -15d-12=-14d | | 3f-2+f-6= | | -5x+18+3(x-1)=8x-(7x-9)-6x+6 | | -4v-9=-6-v | | 12+50-14= | | -4(x+2)-44=8-36 | | 3x+13+3=2xsquared | | 10x=4(-2x+9) | | 6-5y=-4-6y | | 4x-2+3x= | | 46h=4h^3+5h^2 | | -7x-11y-5x+15y= | | -5x+18-3(x-1)=8x-(7x-9)+6x+6 | | V(x)=33x+162findx | | 12z+17=11z | | C=38.17+0.50 | | 2z^8/7z^7 |